Perspectives of migrant men who have sex with men and professionals on personal, social and structural barriers and facilitators to sexual healthcare access and outreach strategies: A qualitative study - Chrissy PB Moonen; Christian JPA Hoebe; Casper DJ den Heijer; Jill Buursma; Marita ILS Werner; Ymke J Evers; Nicole HTM Dukers-Muijrers (Journal of Migration and Health, 2025)
Background: Migrant men who have sex with men (mMSM) carry a disproportionate burden of sexually transmitted infections (STIs) yet encounter unique barriers to accessing sexual healthcare. This qualitative study explored mMSM’s and professionals’ perspectives regarding mMSM’s personal, social and structural barriers and facilitators to Dutch sexual healthcare access and outreach strategies. Methods: A qualitative study was conducted using semi-structured interviews with 15 mMSM (aged ≥16) and 10 professionals from various organisations working with mMSM. mMSM were recruited via sexual health nurses at three STI clinics of a Dutch Public Health Service and flyers; professionals via email, flyers, and the project team’s network. Transcripts were analysed thematically using deductive and inductive coding by two researchers, ensuring intercoder agreement. Results: Key facilitators for sexual healthcare access included supportive social networks, in-person consultations, and culturally and LGBTQ+-sensitive staff. Main barriers involved fear of stigma rooted in cultural and religious beliefs, limited awareness of available services, and language-related challenges. Suggested outreach strategies included dating app advertisements, short multilingual videos, and translated posters in venues frequented by mMSM (e.g., bars and schools). Notably, most participants accessed services through personal referrals, underlining the importance of including social networks in outreach strategies. Conclusions: Addressing personal, social and structural barriers while enhancing facilitators contributes to more inclusive and equitable sexual healthcare services. Besides, increasing reach of mMSM through the dissemination of tailored information via social networks, digital platforms, and community settings further supports this objective. These findings inform strategies aimed at reducing health disparities and contribute to broader STI, HIV, and hepatitis prevention goals.